Erotic Geographies in Ancient Greek Literature and Culture - Gilhuly, Kate (Taylor and Francis, 2017)
Cover -- Half Title -- Title Page -- Copyright Page -- Table of Contents -- Acknowledgments -- Introduction: The erotics of place -- Notes -- 1. Corinth, courtesans and the politics of place: Bewitching arts of the courtesans -- Servant to strangers -- The gender of Corinth -- The gender of work -- Not for every man is the voyage to Corinth -- The courtesan has legs: the afterlife of Lais -- Notes -- 2. Medea in Corinth -- Notes -- 3. Laconic sex -- Act like a Spartan, sexually speaking -- The Spartan image -- Thermopylae -- Keeping the barbarian out -- Spartan pederasty: impervious or not? -- Is the womb a tomb? -- Female excess -- Notes -- 4. Lyric poetry, rape and Spartan song on the comic stage -- Spartan men in Lysistrata -- Spartan women in Lysistrata -- The introduction of Lampito -- Diallage -- Notes -- 5. Lesbians are not from Lesbos -- Images of Lesbos: erotics and gender -- Courtesans, music, and geography -- Metaliterary heteroerotics -- Roman Sappho -- The courtesan's contribution to lesbian sexuality -- Notes -- 6. Lesbos and the invention of heterosexuality in Longus' Daphnis and Chloe -- Situating Daphnis and Chloe -- The novel as topograph -- Place and genre -- The plot -- Sappho -- Phatta -- Syrinx -- Echo -- Chloe -- Notes -- Bibliography -- Index.